Penilaian dan Pengukuran Hasil Belajar Mengajar Perspektif Psikologi Perkembangan - Putri, Shanas Septina; YS, Arbaiyah; Maftuhah, Siti; Sumiyati, Siti (Lembaga Yasin AlSys, 2023)
This article discusses the importance of evaluating and measuring teaching and learning outcomes from a developmental psychology perspective. Developmental psychology plays an important role in understanding how people learn and develop over time and in identifying the factors that influence learning outcomes. This article discusses several developmental psychology theories that are important for the evaluation and measurement of learning outcomes, the methods used in the evaluation and measurement, as well as challenges and solutions for the evaluation and measurement of learning outcomes. Hopefully, this article can provide new knowledge for teachers and researchers about how to optimize the teaching and learning process and improve student learning outcomes. Evaluation is a process or activity that provides information about the quality, quantity, and meaning of an observed phenomenon or event. Thorndike defines measurement as the process of generating quantitative information about the nature or characteristics of an object, event, or individual through measurement. According to Thorndike, measurement is the process of producing objective quantitative information about the trait or characteristic being measured. According to Gronlund (2006), teaching and learning outcomes are students' abilities to apply knowledge, skills, and attitudes learned in real-life situations. According to Mulyasa (2013), teaching and learning outcomes are the attainment of learning objectives as measured by students' knowledge, skills, and attitudes. According to Papalia and Feldman (2011), developmental psychology studies the changes that occur in humans during their life span, from childhood to old age.